Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
so thi sis really simple since you have an equal sign so
(n/3)-(5n/6)=1/3
to subtract fractions, make the bottom number the same
n/3 times 2/2=2n/6
(2n/6)-(5n/6) or (2n-5n)/6 so
-3n/6=1/3
multiply both sides by 6
-3n=6/3=2
-3n=2
divide both sides by 3
-n=2/3
mmultiply boht by -1
n=-2/3
tada
n=-2/3
(n/3)-(5n/6)=1/3
to subtract fractions, make the bottom number the same
n/3 times 2/2=2n/6
(2n/6)-(5n/6) or (2n-5n)/6 so
-3n/6=1/3
multiply both sides by 6
-3n=6/3=2
-3n=2
divide both sides by 3
-n=2/3
mmultiply boht by -1
n=-2/3
tada
n=-2/3
[tex]\frac { n }{ 3 } -\frac { 5n }{ 6 } =\frac { 1 }{ 3 } \\ \\ n\left( \frac { 1 }{ 3 } -\frac { 5 }{ 6 } \right) =\frac { 1 }{ 3 } \\ \\ n\left( \frac { 2 }{ 6 } -\frac { 5 }{ 6 } \right) =\frac { 1 }{ 3 }[/tex]
[tex]\\ \\ -\frac { 3 }{ 6 } n=\frac { 1 }{ 3 } \\ \\ -\frac { 1 }{ 2 } n=\frac { 1 }{ 3 } \\ \\ \frac { 1 }{ 2 } n=-\frac { 1 }{ 3 } \\ \\ 2\cdot \frac { 1 }{ 2 } n=-\frac { 1 }{ 3 } \cdot 2\\ \\ n=-\frac { 2 }{ 3 } [/tex]
[tex]\\ \\ -\frac { 3 }{ 6 } n=\frac { 1 }{ 3 } \\ \\ -\frac { 1 }{ 2 } n=\frac { 1 }{ 3 } \\ \\ \frac { 1 }{ 2 } n=-\frac { 1 }{ 3 } \\ \\ 2\cdot \frac { 1 }{ 2 } n=-\frac { 1 }{ 3 } \cdot 2\\ \\ n=-\frac { 2 }{ 3 } [/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.